HAEMODYNAMICS OF FEMORO-POPLITEAL “BY-PASS” SURGERY USING FINITE ELEMENT ANALYSIS METHOD - Sekulić, Dragan; Tomic, Aleksandar; Milasinovic, Danko; Nikolic, Dalibor; Paunovic, Dragana; Miladinovic, Uros; Sekulic, Igor; Maja Savic Sekulic, Maja; Milev, Bosko (Medicinski časopis, 2021)
Introduction. Femoro-popliteal "by-pass" is indicated in the advanced stage of peripheral arterial occlusive disease. Indications for surgical treatment are set on the basis of the clinical exam, "ankle-brachial index" and angiographic findings. Using the finite element analysis method, three-dimensional models can be made on the basis of aniography, on which we can measure different physical quantities and calculate the value of the "ankle-brachial index". Aim. Show the hemodynamics of arteries by the finite element analysis method based on preoperative and postoperative aniography as well as physical quantities that can be measured in this way. Material and method. This case shows the hemodynamics of femoro-popliteal "by-pass" in the preoperative and postoperative model. The models obtained by finite element analysis show: pressure, shear stress, velocities and streamlines. The pressure, ie the "ankle-brachial index", were compared with the values ​​measured on the patient, and the other three values ​​were compared preoperatively and postoperatively. Results. Postoperatively, higher values ​​of pressure and "ankle-brachial index" were measured on the patient and on the models. Wall shear stress and velocity values are reduced, on postoperative models. The streamlines show a dominant anterior tibial artery. Conclusion. The values ​​of physical quantities measured on patient and on models obtained by the finite element analysis method correlate significantly. Some physical quantities could indicate the "weak points" of a particular model.
Keywords: Peripheral arterial occlusive disease; Femoro-popliteal by-pass; Finite element analysis